Professionalism in the Information and Communication Technology Industry - Weckert, John (ANU Press, 2013)
Professionalism is arguably more important in some occupations than in others. It is vital in some because of the life and death decisions that must be made, for example in medicine. In others the rapidly changing nature of the occupation makes efficient regulation difficult and so the professional behaviour of the practitioners is central to the good functioning of that occupation. The core idea behind this book is that Information and Communication Technology (ICT) is changing so quickly that professional behaviour of its practitioners is vital because regulation will always lag behind.